Casta(s), “sociedad de castas” e indigenismo: la interpretación del pasado colonial en el siglo XX - Laura Giraudo (Nuevo mundo - Mundos Nuevos, 2018)
Despite some recent critical voices, the Latin American colonial society is generally characterized as a “society of castes”. The popularization of this interpretation resulted in a number of cliché, being the more remarkable one the idea of a racial hierarchy in the colonial society and, as a consequence, the idea of a “colonial racial legacy” in the contemporary society. The article explores the emergence and consolidation of the idea of a “society of castes”, analyzing the debate around casta(s) and its use in social sciences, the relevant role played by some specific authors in the 1940s (Ángel Rosenblat and Gonzalo Aguirre Beltrán), and the use of casta(s) among indigenistas. The evidence suggests that it probably was in the 1940s, due to the work of social scientists, when the presence of castas and of a casta terminology came to entail the existence of a “system of castes”, or a society founded in a racial segregation. Meanwhile, in the indigenista field, regardless of the use of casta(s), the emergence of a powerful image of the past, stressing colonial continuity from Conquest to present-day, was critical to the “description” of Latin America and its peoples.